Future Tests of Motivated Distance Perception From Multiple Perspectives. (April 2016) - Balcetis, Emily
In response to comments, I repeat and further support the proposal that valence and arousal cannot serve as independent factors of motivated distance perception, but can be incorporated into the model as features of motivational direction. I articulate the importance of eliciting experiences to predict the direction of motivational direction, suggest additional ways to measure motivational direction, and direct the reader to extensive literatures that have illustrated conditions that give rise to approach and avoidance. Finally, I conjecture on how the motivated distance perception model can be further developed.